PENERAPAN GEOFENCING SEBAGAI SISTEM PENGAWASAN PASIEN - Hafidh Hidayat; Waru Djuriatno; Muhammad Aswin (Jurnal Mahasiswa TEUB, 2023)
Surveillance is necessary in the medical world, especially in the case of diseases with high transmission rates. Quarantine is imposed on people who have infected to prevent transmission. In the quarantine process, surveillance plays an important role in keeping the position of people who are under quarantine in the permitted zone, to do that, a device can be used to detect the location of these people and provide warnings if someone leaves the quarantine zone. Geofencing is defined as a perimeter for real-world geographic areas. The term geofencing refers to the technology to draw virtual boundaries on maps and trigger certain actions based on the boundaries. The application of geofencing in this research uses the radius method with a circle-shaped geofencing zone and the center point of the circle as a reference. If the distance of the object from the center point is greater than the radius of the geofencing zone, it indicates that the object is outside the geofencing zone. When the object coordinates exceed the specified radius (radius of the circle) then the system will trigger the apps to bring up a notification, so that the supervisor can act immediately. The application of geofencing can simplify the surveillance process because the supervisor can know exactly the location of the person being surveilled and can quickly take action if someone leaves the geofencing zone. Keyword: Geofencing, Geofence, Surveillance, GPS